Effect of different carbon sources on growth, non-specific immunity and digestive enzyme activity of amur carp (Cyprinus rubrofuscus Lacepede 1803) fingerlings in biofloc based rearing system using inland saline groundwater - Ezhilarasi, V.; Verma, A. K.; Babitha Rani, A. M.; Harikrishna, V.; Chandrakant, M. H.; Ahmad, Irshad; Nageswari, P. (Indian Journal of Fisheries, 2019)
The study was conducted to evaluate the effect of different carbon sources in biofloc based system for rearing amur carp (Cyprinus rubrofuscus Lacepede 1803) fingerlings in inland saline groundwater. The study was undertaken in a complete randomised design (CRD) where each treatment was performed in triplicate. The experimental unit consisted of four different carbon sources viz., T1 (tapioca flour), T2 (wheat flour), T3 (rice bran), T4 (jaggery) and control (C) with water exchange for a duration of 45 days. Each tank (500 l) was stocked with 30 fingerlings with an average body weight of 11.17±0.34 g. At the end of the rearing period, biofloc based treatments showed significantly better growth performance compared to control. Among the treatments, jaggery based biofloc system showed the highest biomass (629.4±1.58 g), specific growth rate, SGR (1.32±0.03 % day-1), protein efficiency ratio, PER (0.29±0.05), and lowest feed conversion ratio, FCR (0.56±0.03). Digestive enzymes of the biofloc reared fishes showed enhanced activity compared to control group. Jaggery based biofloc (T4) showed significantly higher non-specific immune response in terms of respiratory burst activity (1.14±0.01), superoxide dismutase (44.59±0.19 U mg protein-1) and catalase (1.59 ± 0.01 U mg protein-1) activity compared to other biofloc treatments and the control. The present study concluded that jaggery is best as compared to others carbon sources tested (tapioca flour, wheat flour and rice bran) for better growth, non-specific immunity and digestive enzyme activity of amur carp fingerlings in biofloc based rearing system using inland saline groundwater. Keywords: Amur carp, Biofloc, Jaggery, Inland saline groundwater, Carbon Sources, Non-specific immune parameters